2004
DOI: 10.1002/zaac.200400084
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Ph2P(CH2Py)(NSiMe3) and the Staudinger Reaction of Ph2P(CH2Py) with Hydrogenazide1)

Abstract: A new polymorph of the iminophosphorane Ph2P(CH2Py)(NSiMe3), (1), is compared to a just recently published. The reaction of the starting material, the phosphane Ph2P(CH2Py) with N3SiMe3 in the presence of water gives [Ph2P(CH2Py)(NH2)][N3], (2). A comparison of the structural and NMR parameters of 2 with previously reported derivatives of 1, suggests that 2 is best described as a phosphonium salt in which the negatively charged imino nitrogen atom is protonated, according to [Ph2(CH2Py)P+—NH2][N3]—, rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…30 The Li2-P1 distance of 2.6425(19) A ˚is slightly longer than the average Li-P distances in Li(P-C-C N) systems (2.520 A ˚). 18 The acute N2-Li2-P1 angle of 76.79 (6) • is typical for such systems (73.10-87.35 • ). 28 It is easily possible to modify the ligand structure by introducing different substituents at the sulfur atom.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The Li2-P1 distance of 2.6425(19) A ˚is slightly longer than the average Li-P distances in Li(P-C-C N) systems (2.520 A ˚). 18 The acute N2-Li2-P1 angle of 76.79 (6) • is typical for such systems (73.10-87.35 • ). 28 It is easily possible to modify the ligand structure by introducing different substituents at the sulfur atom.…”
Section: Methodsmentioning
confidence: 99%
“…Anisotropic displacement parameters are depicted at the 50% probability level, hydrogen atoms are omitted for clarity. Selected bond lengths [A ˚] and angles [ • ]: S1-N1 1.6144(9), S1-N2 1.6351(9), S1-C9 1.8406(11), P1-C9 1.8403(11), Li1-N1 1.939(2), Li1-N2 2.398(2), Li2-P1 2.6425(19); N1-S1-N2 104.74(5), N1-S1-C9 106.38(5), N2-S1-C9 100.60(5), Li1-N2-Li2 69.23(7), N1-Li1-N2 71.93(7), N2-Li2-P1 76.79(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electron density studies have also shown that the nitrogen -phosphorus bond tend to be more like a single bond than a double bond with a negative partial charge at the nitrogen and a positive one at the phosphorus atom forming a typical nitrogen-ylid-compound. [28] Such small adjustments to the base ligand lead to the general tripodal iminophosphorane ligand system shown in Figure 1.3.2 that was used in this work. The ligand system itself consists of a carbon atom at the connecting backbone position which bridges the three ligand arms and is further substituted with a methyl-group.…”
Section: 3 Tripodal Iminophosphorane Ligand Systemsmentioning
confidence: 99%
“…Because of the ylid like bond between the nitrogen and the phosphorus the nitrogen gets a negative partial charge further improving its tendency to coordinate towards different metal atoms. [28] The electronic properties around the nitrogen coordination site as well as the steric demands of the whole ligand can be adjusted by employing different substituents at the phosphorus atom.…”
Section: 3 Tripodal Iminophosphorane Ligand Systemsmentioning
confidence: 99%